Mohambi xylophone music of the Shangana-Tsonga - Johnston, Thomas F. (International Library of African Music, 1973)
The Tsonga of Mozambique and South Africa are located between the Venda in the northwest and the Chopi in the southeast. While the large Venda xylophones have all but disappeared in the last forty years, Chopi xylophone playing is widely practised and the Chopi orchestras are famous both in the homeland and in the Johannesburg gold-mine compounds. It is on the Chopi timbila that the Tsonga model their mohambi xylophone, often obtaining the ready-made slats by barter and then assembling a copy of the rest of the instrument themselves
Keywords: African Music